Disentangling introspective and exteroceptive attentional control from emotional appraisal in depression using fMRI: A preliminary study - Smith, Ryan; Baxter, Leslie C.; Thayer, Julian F.; Lane, Richard D. (Psychiatry research. Neuroimaging, 2016)
The neurocognitive abnormalities in affective experience associated with depression remain incompletely understood. We examined BOLD activity in 10 healthy and 10 depressed subjects while they viewed emotional picture sets and categorized their experience in the moment as pleasant, unpleasant or neutral (introspective attention), as well as when they viewed matched pictures and judged whether they depicted indoor or outdoor scenes (exteroceptive attention). Contrasts permitted investigation of differences in neural activity between groups associated with (1) attentional control, and (2) appraisal of valence. Introspective attentional control (compared to exteroceptive attentional control) activated a common pregenual anterior cingulate (pACC) region in depressed and control subjects. Contrasts between appraised valences of attended emotional responses revealed a consistent pattern of increased BOLD activity to unpleasant emotional responses and decreased BOLD activity to pleasant emotional responses in depressed subjects relative to controls in ventromedial prefrontal cortex and insula. These findings support the conclusion that mechanisms for conscious attention to emotional experiences are intact in depressed subjects and that the affective disturbance in MDD is related to altered reactivity to pleasant vs. unpleasant stimuli. •Introspective attentional control mechanisms may be intact in major depression (MD).•VMPFC may be under-activated by positive emotional valence in MD.•VMPFC may be over-activated by negative emotional valence in MD.•Exteroceptive attentional control may not reduce bottom-up emotional attention in MD.